Identification of the Er1 resistence gene and RNase S-alleles in Malus prunifolia var. ringo rootstock (Scientia Agricola, 2015)
Woolly apple aphid (WAA; Eriosoma lanigerum Hausm.) is a major insect pest that has significant economic impact on apple growers worldwide. Modern breeding technologies rely on several molecular tools to help breeders select genetic determinants for traits of interest. Consequently, there is a need for specific markers linked to the genes of interest. Apple scions and rootstocks have an additional barrier to the introduction of pest resistance genes due to the presence of self-incompatibility S-RNase alleles. The genetic characterization and early identification of these alleles can amplify the contribution of a breeding program to the selection of resistant genitors that are as compatible as possible. In this study, we identified the Er1 gene involved in the resistance to WAA in Malus prunifolia var. ringo, also known as ‘Maruba Kaido’ rootstock, and we analyzed the inheritance pattern of the WAA resistance Er1 gene in a segregant population derived from Malus pumila ‘M.9’ and ‘Maruba Kaido’ rootstocks. The self-incompatibility of S-RNase alleles S6S26 of ‘Maruba Kaido’ were also identified along with their inheritance pattern. We also confirmed the identification of the S1S3 alleles in the ‘M.9’ rootstock. To the best of our knowledge, this is the first study to characterize WAA resistance and RNase S-alleles in ‘Maruba Kaido’. Furthermore, we discuss the potential use of the genetic markers for these genes and their potential impact on apple breeding programs.